(untitled) (Journal of Applied Learning and Teaching, 2018)
There is something singularly ghastly about clichés when used by educational establishments. By definition, such institutions really ought to know better. But they don’t. So it is that my former school proclaims itself today, on its website, as a ‘forward thinking … educational community’ that promotes ‘values of respect and co-operation’. What a load of old cobblers. I prefer the 1950s model, when the shabbily gowned teachers (exclusively male and ex-military) exercised the cane and threw chalk at miscreants in a richly backward-thinking obsession with corporal punishment. The fabric of the gloomy old joint was largely driven by disrespect and dislocation. It bred a tougher carapace for the vicissitudes of life, though, than the soft-shell product of today’s touchy-feely forward-bloody-thinking. Nevertheless, I must concede that there was one spectacular instance of beneficence in those times past. The Latin master was renowned for his unusual largesse. In his secondary role as the fulcrum of the drama society, he would have us round to his house, fill us up with his home-made wine (concocted from gooseberries, raspberries, strawberries) and send us unsteadily into the night proclaiming Shakespeare to the stars. No-one complained.